The other side of history : daily life in the ancient world - Garland, Robert, 1947-; Teaching Company (Chantilly, VA : Teaching Co., 2012)
People who are anonymous and whose lives are usually ignored in traditional historical accounts are no less important than more prominent individuals in influencing the flow of events. These ordinary, but often heroic, people are the focus of this course. Each of these lectures looks at history from a nontraditional perspective, that of the weak and marginalized-- the poor, sick, disabled, and elderly, as well as the refugees, slaves, women, children, and common soldiers.
Lecture 1. Taking on the other side of history -- lecture 2. Being Paleolithic -- lecture. 3. Living in Mesopotamia -- lecture 4. Being Egyptian -- lecture 5. Belonging to an Egyptian family -- lecture 6. Practicing Egyptian religion -- lecture 7. Being a dead Egyptian -- lecture 8. Being an Egyptian worker -- lecture 9. Being Minoan and Mycenaean -- lecture 10. Being Greek -- lecture 11. Growing up Greek -- lecture 12. Being a Greek slave -- lecture 13. Being a Greek soldier or sailor -- lecture 14. Being a Greek woman -- lecture 15. Relaxing Greek style -- lecture 16. Being a Greek refugee -- lecture 17. Being a sick or disabled Greek -- lecture 18. Practicing Greek religion -- lecture 19. Being an old Greek -- lecture 20. Being a dead Greek -- lecture 21. Being Persian -- lecture 22. Living in Hellenistic Egypt -- lecture 23. Being Roman -- lecture 24. Being a Roman slave -- lecture 25. Being a Roman soldier -- lecture 26. Being a Roman woman -- lecture 27. Being a poor Roman -- lecture 28. Being a rich Roman -- lecture 29. Being a Roman celebrity -- lecture 30. Being a Roman criminal -- lecture 31. Relaxing Roman style -- lecture 32. Practicing Roman religion -- lecture 33. Being Jewish under Roman rule -- lecture 34. Being Christian under Roman rule -- lecture 35. Being a Celt in ancient Britain -- lecture 36. Being a Roman Briton -- lecture 37. Being Anglo-Saxon -- lecture 38. Being a Viking raider -- lecture 39. Living under Norman rule -- lecture 40. Being medieval -- lecture 41. Being poor in the Middle Ages -- lecture 42. Being a medieval woman -- lecture 43. Being a medieval Christian or heretic -- lecture 44. Being a medieval knight -- lecture 45. Being a Crusader -- lecture 46. Being a Pilgrim -- lecture 47. Relaxing medieval style -- lecture 48. Daily life matters.
Compact discs.
In four containers (19 cm.).
Course no. 3810; issued In four containers (19 cm.) as a four volume set of 48 half-hour lectures on 24 discs.
Accompanying course guidebook includes bibliographical references (p. 352-371).
Teaching Co.: IC3810A-01--IC3810A-04.
Lecturer: Robert Garland, Colgate University.
Keywords: Civilization, Western; Civilization -- History; Manners and customs -- History; Mediterranean Region -- Civilization; Europe -- Civilization; Middle East -- Civilization